Self-sampling in Human Papillomavirus screening during and post-COVID-19 pandemic - Cheng Siang, Tan; Zul Hisyam, Fikri Ismail; Abigail Rembui, Jerip; Mardiana, Binti Kipli (Malaysia Medical Association, 2021)
Introduction: Cervical cancer is the third most common cancer among Malaysian women. Sarawak, the largest state in Malaysia has consistently recorded the highest cervical cancer rate in the country where nearly half of its population still live in the rural areas and is at increased risk of the disease due to inequitable access to healthcare. The countrywide lockdown due to the COVID-19 pandemic had halted the accessibility to cervical cancer screening programme. The aim of the study is to determine the feasibility of providing primary HPV DNA test using the selfsampling method to the hard-to-reach population in the interior of Sarawak during the COVID-19 pandemic. Materials and Methods: This is a cross-sectional study where women aged between 20-80 years were recruited via convenient sampling from villages in Long Banga, Sarawak over a five-day outreach programme. Cervicovaginal selfsamples were obtained and screened for the presence of high-risk human papillomavirus DNA (HR-HPV) using the careHPVTM Test. A self-administered questionnaire was also administered to determine the sociodemographic and perception towards the self-sampling method. Results: The 55 women recruited consist of ethnic backgrounds of Penan (58.18%), Kenyah (25.45%), Iban (5.45%), Saban (3.64%), Kelabit (3.64%), Malay (1.82%) and Chinese (1.82%). The prevalence of HR-HPV was 1.85% (n=1/55). Nearly 80% of the women were unemployed, and more than half have had attended primary education. Nine (16.4%) have heard about HPV, and seven (13%) knew HPV infection could cause cervical cancer. Three of them had HPV vaccination, and only one (1.85%) knew the brand of the HPV vaccine. Although 40% preferred self-sampling over clinician-collection, only ten (18.2%) women have completed the self-collection perception questionnaire. Conclusion: Primary HPV DNA screening using the self-sampling method can be carried out in the remote areas during the COVID-19 pandemic without compromising mobility restriction